Graphene nanoplatelets promoted CoO-based catalyst for low temperature CO2 methanation reaction - Zhong, Liping; Pham, Thi Ha My; Ko, Youngdon; Züttel, Andreas (Frontiers in Chemical Engineering, 2023)
Methanation of CO2 is an important reaction for reducing CO2 emissions in a power-to-gas system. Compared to cobalt supported on gamma-Al2O3, cobalt supported on graphene nanoplatelets (GNPs) showed significantly better performance for CO2 methanation. Cobalt supported on GNPs was capable of 15% conversion of CO2 to CH4 at temperatures below 250°C, compared to 5% for cobalt supported on Al2O3. In situ thermogravimetric analysis (TGA) demonstrated that the Co/GNP catalyst was stable to 400°C. The maximum catalyst mass-specific CH4 yield was obtained at a Co loading of 5wt% on GNPs; however, high Co loading on GNPs deactivated the reactivity of the Co/GNP catalyst. Transmission electron microscopy (TEM) demonstrated that 5wt% Co/GNPs had the smallest and most dispersed cobalt nanoparticles. Excessive loading of cobalt tended to form isolated large Co nanoparticles. X-ray photoelectron spectroscopy (XPS) and Raman spectrometry revealed that more CoO phases were maintained on the surface of 5wt% Co/GNPs, indicating that the interaction between the Co and the GNPs had more of an impact on cobalt’s redox capacity than did particle size, which ultimately affected cobalt’s active phase during the CO2 reduction process. Furthermore, Raman spectrometry demonstrated that Co loading led to an increase in graphene defects. Higher Co loading on GNPs resulted in fewer interfaces between Co and GNPs due to the agglomeration of Co nanoparticles.